Detection and Analysis Signal Energy of Piston Ring Damages on Four Strokes Engine - Kurniawan, Dondi; Purboputro, Pramuko Ilmu; Siswanto, Waluyo Adi (Prosiding Simposium Nasional Rekayasa Aplikasi Perancangan dan Industri, 2024)
The purpose of this study is to develop the piston ring damage detection technique using vibration analysis. Vibration analysis was performed by measuring vibration in four stroke engine which were worn and scratched on its piston ring, then compare it with the vibrations generated by engine which had a good conditions. Tests carried out on engine rotations of 750, 1500, and 2250 rpm, where the sensor were placed on the cylinder head and cylinder block. Vibration measurement produced a signal in the time domain, which then be analysed their signal energy by manual calculation which based on trapezoidal rule. Result of the research showed that the vibration signal energy decrease in all of the strokes of the defect piston ring. It was caused by the pressure of the defect piston ring smaller than the good piston ring. The decrease of vibration signal energy in suction and compression stroke were greater than the power and exhaust stroke. Indication of piston ring defect could be shown from the decrease in the vibration signal energy in all of the strokes.